Comparative analysis of theoretical models of digital citizen engagement: European experience and Ukrainian realities - Velychko, Larysa; Ignatenko, Lina (Pressing Problems of Public Administration, 2025)
This paper presents a comparative analysis of theoretical models of digital citizen engagement in European and Ukrainian contexts. The research systematises the main theoretical approaches: institutional-procedural, socio-technical, participatory-deliberative, ecosystem-based and innovation-transformational. The Baltic, Scandinavian, Central European, Turkish and Ukrainian models are compared according to criteria of institutional embeddedness, technological integration, socio-cultural contextualisation and transformational potential. The development and implementation of key digital engagement tools are analysed: e-consultations, participatory budgeting, e-petitions and direct democracy platforms. The conceptual foundations for adapting European digital engagement practices to Ukrainian realities are substantiated, taking into account the specifics of transformational processes in the local self-government system. Five adaptation models are proposed: security-oriented digital engagement, integrated civic participation, crisis-adaptive governance, inclusive digital engagement and international integration of digital democracy. The research demonstrates that mechanical copying of even the most successful European models is ineffective without considering Ukraine’s unique context of simultaneous decentralisation, digitalisation and countering external aggression. The findings establish that the most promising approaches for Ukraine are tools and methods that ensure resilience and security under digital threats, adaptability in crisis conditions and inclusivity for overcoming the digital divide. The study substantiates that Ukrainian experience of digital engagement during wartime may offer valuable insights for global digital democracy practices and creates innovative potential for developing new forms of civic participation in complex security environments.